IMPROVING STUDENTS’ READING COMPREHENSION BY USING PICTURE STORIES OF VIII GRADE AT MTS MADINATUL ILMI DDI SIAPO - Mohammad Rafi'i (Universitas Madako Tolitoli, 2019)
This research is pre-experimental research design that aims to find whether or not the implementation of picture stories, and the test methot improve the student’ reading comprehansion of VIII grade at MTs Madinatul Ilmi DDI Siapo which consists of 28 students. In this research used on Pre-test and Pos-test. In the Pre-test was used to measure the students’ previous improving students’ reading comprehansion, the treatment were applaying materials Picrure Stories and the Post-test was used find the students’ reading comprehansion after given treatment. The results of the test show that the student’ mean score in pre-test is (39.89) while in the Post-test improved up to (76.71) the data of this research were analyzed by using SPSS program 16.0. computation of the data T-counted result is (12.825) weach means score was high than T-table result is (2.052). it means that the reading comprehansion of VIII grade at MTs Madinatul Ilmi DDI Siapo is improve Key word : Reading, Comprehansion,Picture Stories